A Novel Role for Raloxifene Nanomicelles in Management of Castrate Resistant Prostate Cancer. (6th February 2014) - Taurin, Sebastien; Nehoff, Hayley; van Aswegen, Thalita; Rosengren, Rhonda J.; Greish, Khaled
Abstract : Of patients with castrate resistant prostate cancer (CRPC), less than 25–33% survive more than five years. Recent studies have implicated estrogen, acting either alone or synergistically with androgens in the development of castrate resistant prostate cancer. Several in vitro and in vivo studies, as well as a limited number of clinical trials, have highlighted the potential of selective estrogen receptor modulators, such as raloxifene (Ral) for the treatment of castrate resistant prostate cancer. However, the poor oral bioavailability and metabolism of selective estrogen receptor modulators limit their efficiency in clinical application. To overcome these limitations, we have used styrene co-maleic acid (SMA) micelle to encapsulate raloxifene. Compared to free drug, SMA-Ral micelles had 132 and 140% higher cytotoxicity against PC3 and DU 145 prostate cell lines, respectively. SMA-Ral effectively inhibits cell cycle progression, increases apoptosis, and alters the integrity of tumor spheroid models. In addition, the micellar system induced changes in expression and localization of estrogen receptors, epidermal growth factor receptor (EGFR), and downstream effectors associated with cell proliferation and survival. Finally, SMA-Ral treatment decreased migration and invasion of castrate resistant prostate cancer cell lines. In conclusion, SMA-Ral micelles can potentially benefit new strategies for clinical management of castrate resistant prostate cancer.